The program of the month (Journal of Parents and Teachers, 2014)
In this month's programme we present Hot Potatoes, a programme that allows teachers to create different interactive tests based on web pages.All you have to do is enter the data, such as questions, texts, answers or images, and the programme will generate a test with all of them.The article explains how you can download it to your computer.
Keywords: ICT; Hot potatoes; networked learning